Factors Affecting Green Growth Policy in Vietnam - Trung, Phan Nhan (Journal of Business Management and Economic Development, 2025)
Green growth is becoming a global priority as countries increasingly recognize the importance of combining economic development with environmental protection. Green growth policies and strategies are designed to reduce greenhouse gas emissions, promote the use of renewable energy, and improve resource efficiency, contributing to the goal of sustainable development and combating climate change. Government green growth policies are influenced by many economic, social, environmental, and political factors that determine the effectiveness and sustainability of these measures. Essential factors include public awareness, international pressure, economic and financial policies, technology and innovation, local environmental issues, politics and leadership, and public-private partnerships (PPPs). Vietnam has implemented the "National Strategy on Green Growth" for 2021-2030 with clear goals and has achieved many significant results, such as reducing greenhouse gas emissions and increasing forest coverage. However, there are still many limitations in terms of capital, technology, and supporting policy mechanisms. By proposing a qualitative research model on influencing factors and quantitative methods, specifically multivariate linear regression analysis, the author has shown the model results of these influencing factors on green growth policy, contributing to proposing recommendations to improve green growth policy in Vietnam.